WANPRESTASI DALAM PERJANJIAN SEWA LAHAN ANTARA PT. SINAR HASIL ALAM DENGAN PEMILIK LAHAN DESA TELUK BAKUNG KECAMATAN SUNGAI AMBAWANG DI KABUPATEN KUBURAYA - MICHAEL ADAM LOUW NIM. A1012191011 (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac This thesis discusses Default in the Land Lease Agreement Between PT. Rays of Natural Products with Land Owners Teluk Bakung Village, Sungai Ambawang District, in Kubu Raya Regency. Where in the Lease Agreement the parties from PT Sinarhasil Alam are Mr. Liu Haichang as the Director of PT. Sinar Produk Alam wants to rent land on the Ambawang River and the land on the Ambawang River belongs to Mr. Khou Nam Kuang as the land owner in Ambawang. The Leasing Party gives a price to the Lessee at a rental price of Rp. 600,000,000.- (six hundred million rupiah) and the Lessee has agreed to this price and has paid a down payment of Rp. 60,000,000.- (sixty million rupiah) before the addendum (agreement) of this Land Lease agreement is signed, using valid proof of payment (receipt).The formulation of the problem in this study is